Politics and Military Administration in the Portuguese Atlantic World - Cruz, Miguel Dantas da (Early Modern History and Modern History E-Books Online, Collection 2025., 2026)
Once seen as an ultra-centralized structure, the Portuguese empire is now often portrayed as a headless entity, coaxed into action by restless overseas subjects. This book proposes a more nuanced approach. Through an in-depth analysis of imperial management structures and practices, this book shows that the military administration of Brazil rested on agreements with colonial polities: the Luso-Dutch war consolidated, for example, an extreme version of municipal autonomy. However, subsequent conflicts and the spectre of revolts expanded metropolitan intervention (long before we are told), although the service of colonial populations remained crucial for the Portuguese military forces.